HERMENEUTICS AND DECONSTRUCTION OF HILÂL TESTIMONY VERSE: Critical View on Q.S. al-Baqarah 185 - Nurkhanif, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This research focuses on the hilâl witness verse contained in Q.S. al-Baqarah [2]:185. Tafsîr scholars such as al-Râzî, al-Marâghî, Ibn Kathîr, and Quraish Shihab have not yet formulated its exegesis comprehensively, especially in these days when many people claim about hilâl witness that is needed to be justified. They only interpreted the verse as limited to the conditions of people who were staying or traveling. Therefore, the author gives other tafsîr styles using hermeneutics and deconstruction methods as well as scientific-astronomical approach; it uses descriptive qualitative research. The result of this research gives legal legitimacy that the accepted hilâl testimony accepted is the one fulfilling fiqh and astronomy criteria. He is not any random person but the one that must have sufficient expertise and ability in rukyat al-hilâl process. This can be seen from the word مَن (man) in Q.S. al-Baqarah [2]:185 which is part of isim al-mawṣûl and isim ma'rifat giving the principle of specificity.